A review on the status of some major fish species in Lake Victoria - Outa, Nicholas; Yongo, Edwine; Keyombe, Jameslast; David, Namwaya (My University, 2019)
Lake Victoria, the second largest freshwater lake in the world supports a huge flora and fauna with a large human population around the Lake. The Lake is a source of food (fish), water for domestic use and crop and livestock production, transportation, tourism among others. Due to its varied uses, human intervention within the lake and its catchment has caused several ecological changes in the recent years with profound effects on the resource resources. One of the most notable change is the reduction and risk of extinction of some fish species, including the endemic tilapiine species (Oreochromis esculentus and O. variabilis), catfishes (Xenoclarias eupogon), haplochromines and cyprinids (Labeo victorianus and Barbus altinialis) within the lake. The reduction in biodiversity and extinctions within the lake has been ascribed to the introduction of alien fish species (Nile perch (Lates niloticus) and Nile tilapia (O. niloticus) into the lake, habitat loss and the cultural eutrophication. These changes if left unchecked will have devastating effects on the lake’s resources and at large to people living around the lake and beyond who depend on the lake for their livelihood. There is, therefore, an urgent need for management measures based on sound scientific research to be taken in order to curb the loss of ichthyodiversity within the lake and to save livelihoods of the direct and indirect dependents of the lake
Keywords: diversity loss; endangered; haplochromines; Lake Victoria